2021
DOI: 10.1016/j.scitotenv.2020.142152
|View full text |Cite
|
Sign up to set email alerts
|

Sorptive removal of disinfection by-product precursors from UK lowland surface waters: Impact of molecular weight and bromide

Abstract: The current study compared the impact of three different unit processes, coagulation, granular activated carbon (GAC), and a novel suspended ion exchange (SIX) technology, on disinfection by-product formation potential (DBPFP) from two UK lowland water sources with medium to high bromide content. Specific attention was given to the influence of the organic molecular weight (MW) fraction on DBPFP as well as the impact of bromide concentration.While few studies have investigated the impact of MW fractions from L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This has been proven by Ruhl et al (2012), who investigated the elution behavior of a large set of low MW acid compounds with LC-OCD-OND and showed that their elution occurs over the entire humic substances peak and not only in the shoulder, which is denoted as the low MW acid peak [23,24]. LC-OCD-OND has been applied in various studies to investigate the performance of drinking water treatment processes and/or to assess the impact of altering NOM characteristics in the source water on these processes [25][26][27][28], e.g., MacKeown et al (2021) found a correlation between trihalomethane formation potential and the concentration of building blocks in the water [26]. A drawback of LC-OCD-OND is that its implementation and data interpretation are still relatively complex, which impedes its use in routine analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This has been proven by Ruhl et al (2012), who investigated the elution behavior of a large set of low MW acid compounds with LC-OCD-OND and showed that their elution occurs over the entire humic substances peak and not only in the shoulder, which is denoted as the low MW acid peak [23,24]. LC-OCD-OND has been applied in various studies to investigate the performance of drinking water treatment processes and/or to assess the impact of altering NOM characteristics in the source water on these processes [25][26][27][28], e.g., MacKeown et al (2021) found a correlation between trihalomethane formation potential and the concentration of building blocks in the water [26]. A drawback of LC-OCD-OND is that its implementation and data interpretation are still relatively complex, which impedes its use in routine analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Humic substances, the most abundant NOM fraction in ground and surface water, are anionic under neutral to basic pH and therefore a good overall removal by anion exchange resins (AER) is expected and experimentally confirmed. For the BP and LMWN fraction, having a lower charge density under these pH conditions, removal using AER is more challenging, resulting in low removal efficiencies [3,8,[14][15][16][17][18]. However, the remaining NOM can be of concern since biopolymers can e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the remaining NOM can be of concern since biopolymers can e.g. be related to the hydrothermolytical formation of organic acids in steam circuits (introducing an increased corrosion risk) [19], fouling in water treatment processes based on membrane filtration [20] and are potential disinfection by-product precursors [17]. "…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation